2016
DOI: 10.1186/s12951-016-0225-6
|View full text |Cite
|
Sign up to set email alerts
|

Pure and multi metal oxide nanoparticles: synthesis, antibacterial and cytotoxic properties

Abstract: Th antibacterial activity of metal oxide nanoparticles has received marked global attention as they can be specifically synthesized to exhibit significant toxicity to bacteria. The importance of their application as antibacterial agents is evident keeping in mind the limited range and effectiveness of antibiotics, on one hand, and the plethora of metal oxides, on the other, along with the propensity of nanoparticles to induce resistance being much lower than that of antibiotics. Effective inhibition against a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
281
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 523 publications
(290 citation statements)
references
References 203 publications
(198 reference statements)
2
281
0
7
Order By: Relevance
“…Also, synthesis of cupric oxide NPs (CuO NPs) with spherical-like shape was carried out by the planetary ball mill method [22]. In return, NPs synthesis through biological techniques specifically applying microorganisms emerged as an eco-friendly, clean and benefit alternative to physicochemical techniques [23]. In recent years, green methods have attained tremendous attention in synthesis of pure or oxide MNPs [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Also, synthesis of cupric oxide NPs (CuO NPs) with spherical-like shape was carried out by the planetary ball mill method [22]. In return, NPs synthesis through biological techniques specifically applying microorganisms emerged as an eco-friendly, clean and benefit alternative to physicochemical techniques [23]. In recent years, green methods have attained tremendous attention in synthesis of pure or oxide MNPs [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, antibacterial activity of copper and copper oxide nanomaterials have limited research, likely due to fast oxidation of metallic copper nanoparticles in exposure to air and both chemical and physical instability of the copper oxides formed at temperature below 200 °C, particularly if Cu 2 + is formed [13,14]. Also, it has been observed that the composites of metal oxides show superior characteristics than that of single one because of the collective behavior of individual entity [15,16]. This is one of the fast-emerging areas of research.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomatter penetration into the environment and the specific activity can cause degradation effects [5]. Accordingly, there is a need of broader studies on the characteristics of the nanoparticles, both in terms of their physicochemical properties and biological activity [6]. It is also necessary to modify the processes for obtaining them, in order to improve the control of these properties or develop such formulas that will not have the harmful activity on living matter or will be limited while maintaining the functionality of materials.…”
Section: Discussionmentioning
confidence: 99%